2011
DOI: 10.2174/157016111794519372
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin: From Forgotten Biomarker to Leading Actor in Cardiovascular Pathophysiology

Abstract: Inflammation plays a role at all stages of atherosclerosis. Neopterin, a pteridine mainly synthesized by activated macrophages, is a marker of inflammation, immune system activation and an active participant in cardiovascular disease. Measurement of neopterin levels may help follow the evolution of specific inflammatory conditions (e.g. viral infection, renal transplant rejection, systemic inflammatory diseases, nephritic syndrome and autoimmune diseases). Serum levels of neopterin are elevated also in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 127 publications
0
49
0
1
Order By: Relevance
“…Thus, we hypothesize that N is useful in identifying the activated process of macrophage cells in patients with chronic PAD. It is known that different biomarkers of inflammation, such as interleukins or metalloproteinases are elevated both in chronic and more severe PAD patients (32)(33)(34)(35)(36)(37)(38). Results of this study have shown the involvement of activated macrophages in chronic arterial disease of the lower limbs, albeit not symptomatic.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, we hypothesize that N is useful in identifying the activated process of macrophage cells in patients with chronic PAD. It is known that different biomarkers of inflammation, such as interleukins or metalloproteinases are elevated both in chronic and more severe PAD patients (32)(33)(34)(35)(36)(37)(38). Results of this study have shown the involvement of activated macrophages in chronic arterial disease of the lower limbs, albeit not symptomatic.…”
Section: Discussionmentioning
confidence: 59%
“…provides information about the cellular immune system activation [53][54][55][56]58] for the purpose of diagnosis, successful treatment and prognosis of inflammatory states, including atherosclerosis [56,59,60], malignancies (cancer and leukemia) [61], vascular (cardiovascular-, brain vascular, peripheral artery vascular) [59,62,63], neurological, autoimmune, and many other socially important diseases [e.g. acquired immune deficiency syndrome (AIDS); other viral and bacterial infections], aging-related disorders, including MS [56,57,60,[64][65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, elevated neopterin concentrations correlated positively with increased plasma levels of hsCRP [69]. However, the direct contribution of CRP to atherogenesis is still unclear and debated [59]. The cellular and molecular mechanisms of a direct involvement of neopterin in atherogenesis through nuclear factor κB (NF-κB) could be better understood and clarified in the future, in view of its great potential as a bone marrow hematopoietic (granulocyte-macrophageal) growth factor, GM-CGF, as well as a bone marrow stromal cell growth factor [33,81,82].…”
Section: Neopterin Testing Is Comparable To That Of Other Inflammatormentioning
confidence: 96%
“…Shedding of CD14 induced by serine proteases leads to a soluble CD14 (sCD14) present in plasma [48]. Neopterin (NPT) is produced in large amounts by human monocytes/macrophages upon stimulation with the cytokine interferon-γ released by activated T-lymphocytes [49]. Whereas mCD14 complex is expressed on macrophages and endothelial cells within the atherosclerotic plaque, plasma sCD14 shows no relation with stable coronary artery disease or carotid IMT [50][51][52][53][54].…”
Section: Soluble Cd14 Neopterin and Atherosclerosismentioning
confidence: 99%